Changes in Zooplankton Communities of Some Lakes of the Republic of Karakalpakstan in an Ecologically Changed Environment - Ismailovna, Turemuratova Gulistan; Salavatugli, Nagmetov Hamid (European Journal of Life Safety and Stability (2660-9630), 2021)
The article talks about the unfavorable situation in zooplankton communities of some lakes of the Republic of Karakalpakstan.